2020
DOI: 10.3390/s20123383
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Soil Management Effect on Crop Productivity and Vegetation Indices Accuracy in Mediterranean Cereal-Based Cropping Systems

Abstract: Mostly, precision agriculture applications include the acquisition and elaboration of images, and it is fundamental to understand how farmers’ practices, such as soil management, affect those images and relate to the vegetation index. We investigated how long-term conservation agriculture practices, in comparison with conventional practices, can affect the yield components and the accuracy of five vegetation indexes. The experimental site is a part of a long-term experiment established in 1994 and is still ong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 93 publications
(97 reference statements)
2
23
0
Order By: Relevance
“…Orsini and colleagues [34] demonstrated on the same site that unfertilized soil with no tillage process (NT0) achieved better performance in terms of the number of kernels per spike (+46%) and grain yield (t ha −1 ) (+48%) than the unfertilized conventional tillage process (CT0). This could likely be ascribable to the higher organic matter (+24.7%) and nitrogen availability (+24.6%) present in the NT soil as a consequence of the repeated years of no-tillage management [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orsini and colleagues [34] demonstrated on the same site that unfertilized soil with no tillage process (NT0) achieved better performance in terms of the number of kernels per spike (+46%) and grain yield (t ha −1 ) (+48%) than the unfertilized conventional tillage process (CT0). This could likely be ascribable to the higher organic matter (+24.7%) and nitrogen availability (+24.6%) present in the NT soil as a consequence of the repeated years of no-tillage management [4].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are not completely in line with those obtained by Seddaiu and colleagues and by Orsini and colleagues. Our hypothesis is that nitrogen content is not only due to the nitrogen administered dose (0, 90 kg N ha −1 and 180 kg N ha −1 ), but that its presence is also linked to the overall rainfall registered in the experimental site during the considered period-the less the rainfall, the less plants are able to absorb and to commute nitrogen in organic matter, especially protein [34]. In fact, it has been recorded that the total rainfall for the month of April 2018 was considerably lower with respect to the historical value, probably contributing to a lack of nitrogen absorption in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…Vegetation was extracted based on the RGB features using the calculated point vegetation index (PVI), as shown in equation (2), where R, G, and B represent the red, green, and blue channel, respectively. The specific constants were determined following [ 25 ]. Unlike the traditional normalization difference vegetation index (NDVI), which requires near-infrared information, PVI only requires the RGB information.…”
Section: Methodsologymentioning
confidence: 99%
“…Satellites images are refined by assimilating UAV multispectral data with a convolutional neural network. UAV multispectral images were also applied in [ 17 ] for investigating the impacts of long-term conservation agricultural practices on crop yield as well as on vegetation indices. The results showed that soil management affects the vegetation indices accuracy, which is related to the nitrogen nutrition status.…”
Section: Contributionsmentioning
confidence: 99%